2012
DOI: 10.1136/jnnp-2011-301782
|View full text |Cite
|
Sign up to set email alerts
|

Motor axonal excitability properties are strong predictors for survival in amyotrophic lateral sclerosis

Abstract: Axonal persistent sodium currents, estimated by SDTC and latent addition, are strong and independent predictors for shorter survival in patients with ALS. Membrane hyperexcitability is possibly associated with motor neuronal death, and modulation of excessive sodium currents could be a novel therapeutic option for ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 30 publications
3
69
0
1
Order By: Relevance
“…Hyperexcitability of MNs in ALS has been shown in vitro and in vivo [87, 99, 118, 186]. However, it has been reported that if any shifts are observed at all, they point towards overall hypoexcitability, irrespective of MN subtype [39].…”
Section: Differential Vulnerability Between Spinal Motor Unitsmentioning
confidence: 99%
“…Hyperexcitability of MNs in ALS has been shown in vitro and in vivo [87, 99, 118, 186]. However, it has been reported that if any shifts are observed at all, they point towards overall hypoexcitability, irrespective of MN subtype [39].…”
Section: Differential Vulnerability Between Spinal Motor Unitsmentioning
confidence: 99%
“…Changes in axonal excitability evolve with disease progression,57 and may be a predictor of survival in ALS patients 58. Axonal excitability parameters may be useful biomarkers of axonal degeneration.…”
Section: Candidate Biomarkers Of Disease Progressionmentioning
confidence: 99%
“…In terms of clinical-prognostic correlation, one previous study showed that the amount of the SICI decrease correlated with disease duration and motor deficit score 66. However, studies with TT-TMS or NET showed that functional status or survival was instead correlated with peripheral NET or NCS parameters, such as CMAP or strength-duration time constant (SDTC) 45,67…”
Section: Hyperexcitability and Its Clinical Implications In Alsmentioning
confidence: 99%